Study protocol for the use of photobiomodulation with red or infrared LED on waist circumference reduction: a randomised, double-blind clinical trial - Marcelo Marreira; Lidiane Rocha Mota; Daniela Fátima Teixeira Silva; Christiane Pavani (BMJ Open)
Introduction The search for non-invasive procedures to reduce localised adiposity in aesthetics clinics has recently been increasing. In this context, procedures, such as cryolipolysis, ultracavitation, photobiomodulation (PBM) and other techniques have been proposed. Some studies have shown that PBM can be used in body contouring. However, there is no standardisation of the protocol. More than that, as in other techniques for reducing adipose tissue, the availability of triacylglycerol may affect the lipid profile in the blood, bringing consequences to the general health of an individual. This work will aim to compare the light wavelengths when using PBM as a technique for reducing the abdominal waist circumference, while also evaluating the efficacy of the method. Changes in the lipid profile in the blood, with a long-term follow-up, will also be appraised.Methods and analysis This will be a controlled, randomised, double-blind, single-centred clinical trial. 174 patients will be recruited at the Nove de Julho University, Brazil, and then divided into three groups: Group A—RED PBM; Group B—INFRARED PBM; Group C—PLACEBO (Sham) treatment. The treatments will consist of eight sessions, two times a week, for 4 weeks. At each session, the participants will receive 30 minutes PBM (using a radiant exposure of 127 J/cm2), with an abdominal strap containing 4 LED clusters, with 72 devices each, following the indication of randomisation. All of the groups will receive 30 min of Aussie Current, at 4 kHz, modulated at 10 Hz, 40–60 mA. The main outcome of this study will be waist circumference reduction. The secondary variables will be anthropometric data, lipid profile, liver function and adipose tissue thickness, changes in the local microcirculation, and the quality of life and self-esteem. The analyses will be performed at four stages of the research, D0, end of the eighth session (D30), 15 days after the last session (FU15), 90 days after the last session (FU90) and 180 days after the last session (FU180).Ethics and dissemination The Ethics Committee of the Nove de Julho University, Brazil, approved the modified version of this project under No. 3414146 on 26 June 2019. This study is not yet recruiting. The results obtained will be published in a peer-reviewed journal in the related field.Trial registration number Brazilian Registry of Clinical Trials—ReBec (RBR-9bwxcx).